Evaluation of the Antimicrobial Susceptibility of Community-Acquired Urinary Tract Infection - Passadouro, Rui (2014)
Introduction: The urinary tract infections, after respiratory infections, are the most common in the community. The knowledge about the prevalence of microbial strains and their antibiotic susceptibility is crucial to establish an effective empirical therapy. The aim of this study was to determine the antibiotic susceptibility patterns of bacterial strains isolated from positive urine cultures performed in patients from the central region of Portugal.Material and Methods: We carried out a documental analysis of 6008 urine bacteriological exams, to be made available to physicians, most of which run through the automated system VITEK 2, bioMérieux. The majority (80%) of the urine bacteriological exams were from female. Escherichia coli was the most prevalent bacterial pathogen (65.9%), followed by Klebsiella spp (12%).Results: Nitrofurantoin showed high levels of activity (96%) for Escherichia coli, as well as Fosfomycin (96.6%). Amoxicillin-clavulanic acid presents an activity level of only 81.1% for the same germ. Quinolones exhibit efficacy to only 78% of the strains of Escherichia coli, below the Fosfomycin and Nitrofurantoin. Nitrofurantoin showed high levels of activity (96%) for E. coli as well as Fosfomycin (96.6%). Amoxicillin-Clavulanic Acid presents a level of activity of only 81.1% for the same germ. The quinolones have a efficacy for only 78% of strains of E. coli, lower than Fosfomycin.Discussion: Escherichia Coli was the most prevalent uropathogen (65.9%). High efficacy against this pathogenic agent was found for Fosfomycin (96.6%) and Nitrofurantoin (96%).Conclusion: Further antimicrobial surveillance studies should be developed, in order to formulate local empirical therapyrecommendations for optimized therapeutical choices.Keywords: Urinary Tract Infections; Drug Resistance, Bacterial; Anti-Bacterial Agents; Community-Acquired Infections.